Developing and Evaluating the Le-Zoo Board: An Augmented Reality-Based Medium for English Vocabulary Reading among Students with Autism - Yunita Putri Maulidina; Testiana Deni Wijayatiningsih; Dodi Mulyadi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Students with autism may benefit from structured, visually clear, and multisensory English learning materials. This study developed and preliminarily evaluated the Le-Zoo Board, an interactive learning medium integrating a board game, sensory audio, and augmented reality cards for English animal-vocabulary reading. The study employed a research-and-development approach based on the ADDIE model. Participants were 11 students with mild autism from a special school in Yogyakarta, selected through purposive sampling. Data were collected through material- and media-expert validation, a one-group pre-test–post-test, and a student-response questionnaire. Material-expert validation reached 97.6%, and media-expert validation reached 97%, both categorized as very valid. The paired-samples analysis showed a significant pre–post difference (mean difference = -44.545, SD = 9.342, t(10) = -15.815, p < .001). The student-response score was 480 of 550, or 87.27% of the maximum possible score, indicating a positive practicality response. These findings provide preliminary evidence that the Le-Zoo Board is valid, positively received, and associated with short-term improvement in English animal-vocabulary reading. Because the study involved a small one-group sample, causal and comparative interpretations should be made cautiously.